FAKTOR FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR PAJAK WAJIB PAJAK PRIBADI (Students' Journal of Accounting and Banking, 2013)
This study aimed to determine the factors that influence the willingness to pay taxes on a case study of an individual taxpayer who does work in the field of trade registered in KPP Pratama Jepara. The factors that are the willingness in paying the tax, knowledge and understanding of tax regulations, perception of tax system effectivity, and quality of service. This study uses primary data. Data were collected using a questionnaire that is mailed questionnaires were 98 respondents with a sampling area.The analytical tool used is multiple regression analysis to examine the effect of the above variables. The results showed that variable the willingness in paying the tax, knowledge and understanding of tax regulations, and quality of service have a significant influence on the willingness to pay taxes. While a perception of tax system offectivity does not have a significant effect on the willingness to pay taxes.Keywords: The willingness in paying the tax, knowledge and understanding of tax regulations, perception of tax system offectivity, quality of service, and willingness to pay taxes.